2023
DOI: 10.3390/surgeries4030043
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Primary Anterior Cruciate Ligament Reconstruction with Peroneus Longus and Bone–Patellar Tendon–Bone Autografts: A Clinical Comparative Study

Evgeniy Nikolaevich Goncharov,
Oleg Aleksandrovich Koval,
Eduard Nikolaevich Bezuglov
et al.

Abstract: Background: The aim of this study is to compare the mid-term outcomes of primary tear of the anterior cruciate ligament (ACL) reconstruction via the use of peroneus longus tendon (PLT) and bone–patellar tendon–bone (BPTB) autografts. Methods: 53 patients (group 1) received ACL reconstruction via BPTB, whereas 55 patients (group 2) received arthroscopic ACL reconstruction using PLT autograft. Results: In group 1, the mean preoperative and postoperative scores on the Lysholm Knee Questionnaire (LKQ) scale result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, the increased complexity of double-bundle techniques may lead to longer surgical times and a more challenging rehabilitation process. Some studies have found no significant difference in outcomes between single-and double-bundle techniques in the general population, suggesting that the choice should be based on the specific needs and goals of the patient, as well as the surgeon's expertise [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, the increased complexity of double-bundle techniques may lead to longer surgical times and a more challenging rehabilitation process. Some studies have found no significant difference in outcomes between single-and double-bundle techniques in the general population, suggesting that the choice should be based on the specific needs and goals of the patient, as well as the surgeon's expertise [19].…”
Section: Introductionmentioning
confidence: 99%